PEMANTAUAN TEGANGAN LISTRIK TIGA FASE BERBASIS INTERNET OF THINGS PADA TRANSMISI TVRI JAWA TENGAH - noviyanto, hendri; Rianto, Agus; Kusumo, Jalu Dwi (SPIRIT, 2025)
Voltage stability in transmission systems is crucial to ensure uninterrupted television broadcasting, especially in three-phase installations such as those used by TVRI Central Java. Voltage disturbances or overload conditions can damage equipment and disrupt broadcast quality. This study aims to design a three-phase voltage monitoring and control system based on the Internet of Things (IoT), integrated with the Blynk application as a user interface. The system utilizes an ESP32 microcontroller connected to ZMPT101B voltage sensors to monitor each phase in real-time. Data is transmitted via Wi-Fi to the Blynk platform, allowing users to remotely monitor system conditions through a smartphone. Additionally, the system is equipped with an automatic shutdown mechanism using a relay that disconnects the power supply when an overload is detected, preventing potential equipment damage. Test results show that the system performs responsively, provides accurate voltage readings, and effectively executes automatic disconnection when threshold limits are exceeded. This system is expected to significantly enhance monitoring efficiency and protect transmission installations.